The Effect of BTCLS Training on Emergency Knowledge of Dharma Husada Nursing Academy Kediri Graduates - Irawan, Hengky; Susilowati, Erna; Atmojo, Didik Susetiyanto (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Basic Trauma Cardiac Live Support (BTCLS) training for nurses is an effort to improve skills to overcome emergency events that occur outside the hospital due to accidents / trauma or in the hospital due to diseases that impact cardiac arrest. Training is an activity to increase skills, knowledge and skills for nurses in providing appropriate and prompt care to patients. The purpose of the research was to find out the effect of BTCLS training on emergency management knowledge for akper dharma husada kediri nursing alumni. Research design with pre-experimental method with one group pre-post test design approach. . Research samples 50 people with simple random sampling techniques. Data collection used questionnaires and data analysis using t-test. The results obtained a calculated value of 23.25 and a significance value of 0.000. Concluded the influence of BTCLS training on the knowledge of emergency management for graduates.